Preparation method and application of nickel-basalt cathode supported solid oxide electrolytic tank

By combining basalt ore powder with nickel oxide powder, a nickel-basalt cathode-supported solid oxide electrolytic cell is prepared, which solves the problems of complex and high cost of cathode materials in the prior art, and achieves efficient and low-cost electrolytic performance. It is suitable for electrolytic carbon dioxide/water and solid oxide fuel cells.

CN119685846APending Publication Date: 2025-03-25XINJIANG TECH INST OF PHYSICS & CHEM CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411809760.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing solid oxide electrolytic cell cathode materials have complex processes, high costs and difficulty in preparing electrolytic cells with large areas, which limits their large-scale applications. In addition, it is difficult to study the performance of existing cathode materials under high temperature conditions.

Method used

A nickel-basalt cathode-supported solid oxide electrolytic cell is prepared by mixing basalt ore powder with nickel oxide powder, and after grinding, pressing, high temperature treatment and specific atmosphere reduction.

Benefits of technology

The prepared nickel-basalt cathode-supported solid oxide electrolyte cell has high conductivity, high mechanical strength and high porosity, and the current density can reach 631mA/cm2, which significantly reduces the cost of material preparation and improves electrolytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685846A_ABST
    Figure CN119685846A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a nickel-basalt cathode supporting type solid oxide electrolytic cell, and the method comprises the steps of basalt ore pretreatment, preparation of a nickel oxide-basalt cathode supporting body, preparation of slurry, preparation of the nickel-basalt cathode supporting type solid oxide electrolytic cell and the like. Basalt powder and nickel oxide powder are mixed, pressed, calcined and reduced in a specific atmosphere, and the nickel-basalt cathode supported solid oxide electrolytic cell with high conductivity, high mechanical strength and high porosity is prepared. Under the testing condition that the temperature is 750 DEG C, pure carbon dioxide serves as raw material gas, the flow velocity is 100 mL / min, and the applied voltage is 1.6 V, the electrolytic tank shows excellent electrochemical performance, and the current density can reach 631 mA / cm < 2 >; according to the invention, basalt ore powder with physical and chemical characteristics and nickel metal with high catalytic activity are selected as cathode materials, so that the material preparation cost is effectively reduced, the electrolytic efficiency is remarkably improved, and a new path is opened up for development of basalt in the high-performance application field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy and solid oxide electrolytic cell (SOEC), and in particular to a preparation method and application of a nickel-basalt cathode supported solid oxide electrolytic cell. Background Art

[0002] As the global energy crisis and environmental pollution problems become increasingly severe, reducing carbon dioxide emissions and achieving carbon neutrality have become the focus of global attention. In this context, it is particularly urgent to develop carbon dioxide emission reduction and resource utilization technologies. As an all-solid-state energy and material conversion device, high-temperature solid oxide electrolysis cells have attracted widespread attention due to their all-solid-state and modular structure, faster reaction rate, high energy efficiency, low cost, and clean and pollution-free. Driven by renewable electricity, solid oxide electrolysis cells can directly electrolyze carbon dioxide into carbon monoxide and O2, of which carbon monoxide can be used as an energy product and basic chemical raw material, and O2 can be used as rocket propellant and a substance required for life support.

[0003] Although solid oxide electrolytic cell technology has significant advantages in carbon dioxide emission reduction and resource utilization, the development of its cathode materials still faces challenges. For cathode materials, for example, Chinese patent CN111244470A proposes to prepare a YSZ skeleton with micrometer pores on the electrolyte layer of a semi-electrolytic cell, and to prepare perovskite and gadolinium oxide-doped cerium oxide / LSFM-GDC (M = Mn, Cu, nickel) composite nanoparticles by co-impregnation method, cover the YSZ skeleton, and form a new solid oxide electrolytic cell nanocomposite cathode; and Chinese patent CN118007172A proposes to use Fe, carbon monoxide, Pd, Cu, Mo and GDC as catalysts, loaded on a YSZ carrier to form an alloy as a cathode. Applying metals with high catalytic activity to the cathode of a solid oxide electrolytic cell is a method to improve the electrolytic performance, but there are defects in the preparation of materials, such as complex process, high cost, and difficulty in preparing a large-area electrolytic cell, which limits its large-scale application. In addition, the performance study of existing cathode materials under high temperature conditions is relatively difficult, and the preparation cost is high, which is difficult to meet the needs of large-scale industrial operation.

[0004] In view of the above problems, the present invention aims to develop a new type of nickel-basalt cathode supported solid oxide electrolytic cell, which fully utilizes the excellent physical and chemical properties of basalt, such as strong compressive resistance, corrosion resistance, high temperature resistance, etc., to reduce material preparation costs and improve electrolysis efficiency. Summary of the invention

[0005] The purpose of the present invention is to further explore the application of basalt in the field of cathode materials for solid oxide electrolytic cells in view of the shortcomings of the prior art, and to provide a method for preparing a nickel-basalt cathode supported solid oxide electrolytic cell and its use. The method comprises the steps of pretreatment of basalt ore, preparation of a nickel oxide-basalt cathode support, preparation of a slurry, and preparation of a nickel-basalt cathode supported solid oxide electrolytic cell. A nickel-basalt cathode supported solid oxide electrolytic cell with high electrical conductivity, high mechanical strength and high porosity is prepared by mixing basalt powder with nickel oxide powder, pressing, calcining and reducing in a specific atmosphere. Under the test conditions of a temperature of 750°C, with pure carbon dioxide as the raw gas, a flow rate of 100 mL / min and an applied voltage of 1.6 V, the electrolytic cell exhibits excellent electrochemical performance, and the current density can reach 631 mA / cm 2 ; The present invention selects basalt ore powder with excellent physical and chemical properties and nickel metal with high catalytic activity as cathode materials, which not only effectively reduces the material preparation cost, but also significantly improves the electrolysis efficiency, opening up a new path for the development of basalt in high-performance application fields; in addition, the nickel-basalt cathode-supported solid oxide electrolytic cell prepared by the method described in the present invention can be widely used in the electrolysis of carbon dioxide / water and the energy conversion process of solid oxide fuel cells, providing an innovative technical solution for the effective conversion and resource utilization of carbon dioxide.

[0006] The method for preparing a nickel-basalt cathode supported solid oxide electrolytic cell of the present invention is carried out according to the following steps:

[0007] a. Basalt pretreatment: crush the natural basalt ore for 40 minutes, pass through a 100-mesh sieve to obtain basalt powder; then ball-mill the basalt powder for 12-20 hours at a ball-milling speed of 150-300 rpm, pass through a 400-mesh sieve to obtain uniform basalt powder particles;

[0008] b. Preparation of a nickel oxide-basalt cathode support: Grind the basalt powder particles obtained in step a and the nickel oxide powder in an agate mortar until they are evenly mixed, the grinding time is 1 hour, and then use a powder tablet press to press the mixed powder into a disc with a diameter of 40 mm and a thickness of 700-900 μm, the pressing pressure is 80-100 MPa, and the pressing time is 120 seconds; Calcine the disc at 1100-1350° C. for 4-6 hours to obtain a nickel oxide-basalt cathode support, wherein the mass proportion of the nickel oxide powder is 50-80wt%;

[0009] c. Preparation of slurry: doping cerium oxide with samarium 0.2 Ce 0.8 O 2-δas raw material, triethanolamine as dispersant, polyvinyl butyral as binder, dibutyl phthalate as plasticizer, ethanol and butanone as solvent, and then stirred for 1 hour to obtain samarium-doped cerium oxide intermediate layer slurry;

[0010] Yttria-stabilized zirconia is used as a raw material, triethanolamine is used as a dispersant, acrylic resin is used as a binder, polyethylene glycol-400 is used as a plasticizer, ethanol and butanone are used as solvents, and the mixture is stirred for 1 hour to obtain a yttria-stabilized zirconia electrolyte slurry;

[0011] Lanthanum ferrite La doped with cobalt and strontium perovskite materials 0.6 Sr 0.4 Carbon monoxide 0.2 Fe 0.8 O 3-δ As raw material, triethanolamine as dispersant, polyvinyl butyral as binder, dibutyl phthalate as plasticizer, ethanol and butanone as solvent, mixed and stirred for 1 hour to obtain perovskite material cobalt and strontium doped lanthanum ferrite anode slurry;

[0012] d. Preparation of a nickel oxide-basalt cathode supported solid oxide electrolytic cell: spray the samarium-doped cerium oxide slurry prepared in step c onto the nickel oxide-basalt cathode support prepared in step b as an intermediate layer between the cathode and the electrolyte of the solid electrolytic cell, dry at room temperature for 12 hours, and calcine at a temperature of 1100-1350° C. in an air atmosphere for 4-6 hours; then spray the yttria-stabilized zirconium oxide slurry obtained in step c onto the intermediate layer of the solid electrolytic cell as an electrolyte, dry at room temperature for 12 hours, and calcine at a temperature of 1100-1350° C. in an air atmosphere for 4-6 hours. 6h; then spray the samarium-doped cerium oxide slurry obtained in step c on the electrolyte of the solid electrolytic cell as an intermediate layer between the electrolyte and the anode, dry at room temperature for 12h, and calcine at a temperature of 1100-1350°C in an air atmosphere for 4-6h; finally, spray the perovskite material cobalt and strontium-doped lanthanum ferrite slurry obtained in step c on the samarium-doped cerium oxide intermediate layer of the solid electrolytic cell as an anode, dry at room temperature for 12h, and calcine at a temperature of 1100-1350°C in an air atmosphere for 4-6h to obtain a nickel oxide-basalt cathode supported solid oxide electrolytic cell;

[0013] e. Preparation of a nickel-basalt cathode supported solid oxide electrolytic cell: The solid oxide electrolytic cell prepared in step d is sealed with alumina felt in a high-temperature furnace of a special electrolysis test equipment, and the temperature is raised to 750°C at a heating rate of 2-4°C / min, followed by introduction of 5%-10% hydrogen / nitrogen for reduction for 2-4h to obtain a nickel-basalt cathode supported solid oxide electrolytic cell; 100mL / min of carbon dioxide is introduced into the cathode side of the electrolytic cell, and the anode side is exposed to the air to provide voltage for the solid oxide electrolytic cell to electrolyze the carbon dioxide to obtain a nickel-basalt cathode supported solid oxide electrolytic cell.

[0014] The nickel-basalt cathode supported solid oxide electrolytic cell obtained by the method is used in the energy conversion process of preparing electrolytic carbon dioxide / water and solid oxide fuel cells.

[0015] The advantages of the present invention compared to the prior art are:

[0016] (1) The prepared nickel-basalt cathode supported solid oxide electrolytic cell has the characteristics of high conductivity, high mechanical strength and high porosity;

[0017] (2) Basalt has a wide range of thermal expansion coefficients, ensuring thermal compatibility with nickel, and has good chemical stability in a carbon dioxide / carbon monoxide atmosphere;

[0018] (3) Basalt can effectively prevent the agglomeration of nickel metal particles, ensuring the high catalytic activity of nickel, while ensuring the formation of pores with an average pore diameter of 200 nm, thereby controlling the overall structure of the cathode;

[0019] (4) At a test temperature of 750°C, a pure carbon dioxide flow rate of 100 mL / min, and a voltage of 1.6 V, the current density reached 631 mA / cm 2 .

[0020] The present invention discloses a method for preparing a nickel-basalt cathode-supported solid oxide electrolytic cell and its use. The method comprises mixing basalt powder with nickel oxide, and then grinding, pressing, high-temperature treatment, and specific atmosphere reduction to prepare a low-cost, high-performance solid oxide electrolytic cell cathode. Basalt, as a basic volcanic rock, has excellent properties such as strong compressive resistance, corrosion resistance, and high temperature resistance. Through this innovative method, the present invention not only improves the performance of the cathode material, but also provides a new way to achieve the effective conversion and resource utilization of carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a flow chart of the preparation of the nickel-basalt cathode of the present invention;

[0022] Figure 2 This is a scanning electron microscope microstructure diagram of the nickel-basalt cathode of the present invention;

[0023] Figure 3 is the X-ray diffraction spectrum of the nickel-basalt cathode of the present invention;

[0024] Figure 4 The figure shows the relationship between voltage and current density when the nickel-basalt cathode supported solid oxide electrolytic cell of the present invention electrolyzes pure carbon dioxide. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but they are only preferred embodiments of the present invention and do not limit the present invention in any form; therefore, all equivalent changes made according to the features and principles described in the scope of the patent application of the present invention belong to the protection scope of the present invention.

[0026] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:

[0027] Example 1

[0028] a. Basalt pretreatment: crush the natural basalt ore for 40 minutes, pass through a 100-mesh sieve to obtain basalt powder; then ball-mill the basalt powder for 12 hours at a ball-milling speed of 300 rpm, pass through a 400-mesh sieve to obtain uniform basalt powder particles;

[0029] b. Preparation of a nickel oxide-basalt cathode support: Grind the basalt powder particles obtained in step a and the nickel oxide powder in an agate mortar until they are evenly mixed, the grinding time is 1 hour, and then use a powder tablet press to press the mixed powder into a disc with a diameter of 40 mm and a thickness of 900 μm, the pressing pressure is 100 MPa, and the pressing time is 120 seconds; calcine the disc at 1250° C. for 4 hours to obtain a nickel oxide-basalt cathode support, wherein the mass proportion of the nickel oxide powder is 50wt%;

[0030] c. Preparation of slurry: 0.8 g of samarium doped cerium oxide Sm 0.2 Ce 0.8 O 2-δ as raw material, 0.2 ml triethanolamine as dispersant, 0.05 g polyvinyl butyral as binder, 0.2 ml dibutyl phthalate as plasticizer, 2 ml ethanol and 1 ml butanone as solvent, mixed and stirred for 1 hour to obtain samarium-doped cerium oxide intermediate layer slurry;

[0031] 0.8 g of yttria-stabilized zirconia was used as a raw material, 0.2 ml of triethanolamine was used as a dispersant, 0.07 g of acrylic resin was used as a binder, 0.3 ml of polyethylene glycol-400 was used as a plasticizer, 2 ml of ethanol and 1 ml of butanone were used as solvents, and the mixture was stirred for 1 hour to obtain a yttria-stabilized zirconia electrolyte slurry;

[0032] 0.8g of perovskite material cobalt and strontium doped lanthanum ferrite La 0.6 Sr 0.4 Carbon monoxide 0.2 Fe 0.8 O 3-δAs raw material, 0.2 ml triethanolamine as dispersant, 0.05 g polyvinyl butyral as binder, 0.2 ml dibutyl phthalate as plasticizer, 2 ml ethanol and 1 ml butanone as solvent were mixed and stirred for 1 hour to obtain a perovskite material cobalt and strontium doped lanthanum ferrite anode slurry;

[0033] d. Preparation of a nickel oxide-basalt cathode supported solid oxide electrolytic cell: The samarium-doped cerium oxide slurry prepared in step c was sprayed onto the nickel oxide-basalt cathode support prepared in step b as an intermediate layer between the cathode and the electrolyte of the solid electrolytic cell, dried at room temperature for 12 hours, and calcined at 1200°C in an air atmosphere for 4 hours; then the yttria-stabilized zirconium oxide slurry obtained in step c was sprayed onto the intermediate layer of the solid electrolytic cell as an electrolyte, dried at room temperature for 12 hours, and calcined at 1250°C in an air atmosphere. 4h; then spray the samarium-doped cerium oxide slurry obtained in step c on the electrolyte of the solid electrolytic cell as an intermediate layer between the electrolyte and the anode, dry at room temperature for 12h, and calcine at 1200°C in an air atmosphere for 4h; finally, spray the perovskite material cobalt and strontium-doped lanthanum ferrite slurry obtained in step c on the samarium-doped cerium oxide intermediate layer of the solid electrolytic cell as an anode, dry at room temperature for 12h, and calcine at 1200°C in an air atmosphere for 4h to obtain a nickel oxide-basalt cathode supported solid oxide electrolytic cell;

[0034] e. Preparation of a nickel-basalt cathode supported solid oxide electrolytic cell: The solid oxide electrolytic cell prepared in step d is sealed with alumina felt in a high-temperature furnace of a special electrolysis test equipment, and the temperature is raised to 750°C at a heating rate of 4°C / min, followed by introduction of 5% hydrogen / nitrogen for reduction for 2 hours to obtain a nickel-basalt cathode supported solid oxide electrolytic cell; 100 mL / min of carbon dioxide is introduced into the cathode side of the electrolytic cell, and the anode side is exposed to the air to provide voltage for the solid oxide electrolytic cell to electrolyze the carbon dioxide.

[0035] Conclusion: When the voltage is 1.6V, the current density is 32mA / cm 2 , due to the fewer nickel particles, the cathode conductivity is lower and the pores formed are larger.

[0036] Example 2

[0037] a. Basalt pretreatment: crush the natural basalt ore for 40 minutes, pass through a 100-mesh sieve to obtain basalt powder; then ball-mill the basalt powder for 16 hours at a ball-milling speed of 250 rpm, pass through a 400-mesh sieve to obtain uniform basalt powder particles;

[0038] b. Preparation of a nickel oxide-basalt cathode support: Grind the basalt powder particles obtained in step a and the nickel oxide powder in an agate mortar until they are evenly mixed, the grinding time is 1 hour, and then use a powder tablet press to press the mixed powder into a disc with a diameter of 40 mm and a thickness of 700 μm, the pressing pressure is 80 MPa, and the pressing time is 120 seconds; calcine the disc at 1100° C. for 6 hours to obtain a nickel oxide-basalt cathode support, wherein the mass proportion of the nickel oxide powder is 70wt%;

[0039] c. Preparation of slurry: 1g of samarium doped cerium oxide Sm 0.2 Ce 0.8 O 2-δ as raw material, 0.2 ml triethanolamine as dispersant, 0.05 g polyvinyl butyral as binder, 0.2 ml dibutyl phthalate as plasticizer, 2 ml ethanol and 1 ml butanone as solvent, mixed and stirred for 1 hour to obtain samarium-doped cerium oxide intermediate layer slurry;

[0040] 1.3 g of yttria-stabilized zirconia was used as a raw material, 0.2 ml of triethanolamine was used as a dispersant, 0.07 g of acrylic resin was used as a binder, 0.3 ml of polyethylene glycol-400 was used as a plasticizer, 2 ml of ethanol and 1 ml of butanone were used as solvents, and the mixture was stirred for 1 hour to obtain a yttria-stabilized zirconia electrolyte slurry;

[0041] 1g of perovskite material cobalt and strontium doped lanthanum ferrite La 0.6 Sr 0.4 Carbon monoxide 0.2 Fe 0.8 O 3-δ As raw material, 0.2 ml triethanolamine as dispersant, 0.05 g polyvinyl butyral as binder, 0.2 ml dibutyl phthalate as plasticizer, 2 ml ethanol and 1 ml butanone as solvent were mixed and stirred for 1 hour to obtain a perovskite material cobalt and strontium doped lanthanum ferrite anode slurry;

[0042] d. Preparation of a nickel oxide-basalt cathode supported solid oxide electrolytic cell: spray the samarium-doped cerium oxide slurry prepared in step c onto the nickel oxide-basalt cathode support prepared in step b as an intermediate layer between the cathode and the electrolyte of the solid electrolytic cell, dry at room temperature for 12 hours, and calcine at a temperature of 1150°C in an air atmosphere for 6 hours; then spray the yttria-stabilized zirconium oxide slurry obtained in step c onto the intermediate layer of the solid electrolytic cell as an electrolyte, dry at room temperature for 12 hours, and calcine at a temperature of 1250°C in an air atmosphere. 6h; then spray the samarium-doped cerium oxide slurry obtained in step c on the electrolyte of the solid electrolytic cell as an intermediate layer between the electrolyte and the anode, dry at room temperature for 12h, and calcine at a temperature of 1150°C in an air atmosphere for 6h; finally, spray the perovskite material cobalt and strontium-doped lanthanum ferrite slurry obtained in step c on the samarium-doped cerium oxide intermediate layer of the solid electrolytic cell as an anode, dry at room temperature for 12h, and calcine at a temperature of 1150°C in an air atmosphere for 6h to obtain a nickel oxide-basalt cathode supported solid oxide electrolytic cell;

[0043] e. Preparation of a nickel-basalt cathode supported solid oxide electrolytic cell: The solid oxide electrolytic cell prepared in step d is sealed with alumina felt in a high-temperature furnace of a special electrolysis test equipment, and the temperature is raised to 750°C at a heating rate of 2°C / min, followed by introduction of 8% hydrogen / nitrogen for reduction for 2 hours to obtain a nickel-basalt cathode supported solid oxide electrolytic cell; 100 mL / min of carbon dioxide is introduced into the cathode side of the electrolytic cell, and the anode side is exposed to the air to provide voltage for the solid oxide electrolytic cell to electrolyze the carbon dioxide.

[0044] Conclusion: When the voltage is 1.6V, the current density is 631mA / cm 2 The cathode has good conductivity, the formed pores are relatively uniform, the porosity reaches 43%, and the performance of electrolyzing carbon dioxide is the best.

[0045] Example 3

[0046] a. Basalt pretreatment: crush the natural basalt ore for 40 minutes, pass through a 100-mesh sieve to obtain basalt powder; then ball-mill the basalt powder for 20 hours at a ball-milling speed of 150 rpm, pass through a 400-mesh sieve to obtain uniform basalt powder particles;

[0047] b. Preparation of a nickel oxide-basalt cathode support: Grind the basalt powder particles obtained in step a and the nickel oxide powder in an agate mortar until they are evenly mixed, the grinding time is 1 hour, and then use a powder tablet press to press the mixed powder into a disc with a diameter of 40 mm and a thickness of 800 μm, the pressing pressure is 100 MPa, and the pressing time is 120 seconds; calcine the disc at 1100° C. for 4 hours to obtain a nickel oxide-basalt cathode support, wherein the mass proportion of the nickel oxide powder is 60wt%;

[0048] c. Preparation of slurry: 1.5 g of samarium doped cerium oxide Sm 0.2 Ce 0.8 O 2-δ as raw material, 0.2 ml triethanolamine as dispersant, 0.05 g polyvinyl butyral as binder, 0.2 ml dibutyl phthalate as plasticizer, 2 ml ethanol and 1 ml butanone as solvent, mixed and stirred for 1 hour to obtain samarium-doped cerium oxide intermediate layer slurry;

[0049] 1.5 g of yttria-stabilized zirconia was used as a raw material, 0.2 ml of triethanolamine was used as a dispersant, 0.07 g of acrylic resin was used as a binder, 0.3 ml of polyethylene glycol-400 was used as a plasticizer, 2 ml of ethanol and 1 ml of butanone were used as solvents, and the mixture was stirred for 1 hour to obtain a yttria-stabilized zirconia electrolyte slurry;

[0050] 1.5g of perovskite material cobalt and strontium doped lanthanum ferrite La 0.6 Sr 0.4 Carbon monoxide 0.2 Fe 0.8 O 3-δ As raw material, 0.2 ml triethanolamine as dispersant, 0.05 g polyvinyl butyral as binder, 0.2 ml dibutyl phthalate as plasticizer, 2 ml ethanol and 1 ml butanone as solvent were mixed and stirred for 1 hour to obtain a perovskite material cobalt and strontium doped lanthanum ferrite anode slurry;

[0051] d. Preparation of a nickel oxide-basalt cathode supported solid oxide electrolytic cell: The samarium-doped cerium oxide slurry prepared in step c was sprayed onto the nickel oxide-basalt cathode support prepared in step b as an intermediate layer between the cathode and the electrolyte of the solid electrolytic cell, dried at room temperature for 12 hours, and calcined at a temperature of 1100°C in an air atmosphere for 5 hours; then, the yttria-stabilized zirconium oxide slurry obtained in step c was sprayed onto the intermediate layer of the solid electrolytic cell as an electrolyte, dried at room temperature for 12 hours, and calcined at a temperature of 1250°C in an air atmosphere. 5h; then spray the samarium-doped cerium oxide slurry obtained in step c on the electrolyte of the solid electrolytic cell as an intermediate layer between the electrolyte and the anode, dry at room temperature for 12h, and calcine at 1100°C in an air atmosphere for 5h; finally, spray the perovskite material cobalt and strontium-doped lanthanum ferrite slurry obtained in step c on the samarium-doped cerium oxide intermediate layer of the solid electrolytic cell as an anode, dry at room temperature for 12h, and calcine at 1100°C in an air atmosphere for 5h to obtain a nickel oxide-basalt cathode supported solid oxide electrolytic cell;

[0052] e. Preparation of a nickel-basalt cathode supported solid oxide electrolytic cell: The solid oxide electrolytic cell prepared in step d is sealed with alumina felt in a high-temperature furnace of a special electrolysis test equipment, and the temperature is raised to 750°C at a heating rate of 3°C / min, followed by introduction of 10% hydrogen / nitrogen for reduction for 3 hours to obtain a nickel-basalt cathode supported solid oxide electrolytic cell; 100 mL / min of carbon dioxide is introduced into the cathode side of the electrolytic cell, and the anode side is exposed to the air to provide voltage for the solid oxide electrolytic cell to electrolyze the carbon dioxide.

[0053] Conclusion: When the voltage is 1.6V, the current density is 196.27mA / cm 2 , the cathode has good conductivity and the porosity formed is high.

[0054] Example 4

[0055] a. Basalt pretreatment: crush the natural basalt ore for 40 minutes, pass through a 100-mesh sieve to obtain basalt powder; then ball-mill the basalt powder for 18 hours at a ball-milling speed of 200 rpm, pass through a 400-mesh sieve to obtain uniform basalt powder particles;

[0056] b. Preparation of nickel oxide-basalt cathode support: Grind the basalt powder particles obtained in step a and the nickel oxide powder in an agate mortar until they are evenly mixed, the grinding time is 1 hour, and then use a powder tablet press to press the mixed powder into a disc with a diameter of 40 mm and a thickness of 700 μm, the pressing pressure is 90 MPa, and the pressing time is 120 seconds; Calcine the disc at 1350° C. for 6 hours to obtain a nickel oxide-basalt cathode support, wherein the mass proportion of the nickel oxide powder is 80wt%;

[0057] c. Preparation of slurry: 1.5 g of samarium doped cerium oxide Sm 0.2 Ce 0.8 O 2-δ as raw material, 0.2 ml triethanolamine as dispersant, 0.05 g polyvinyl butyral as binder, 0.2 ml dibutyl phthalate as plasticizer, 2 ml ethanol and 1 ml butanone as solvent, mixed and stirred for 1 hour to obtain samarium-doped cerium oxide intermediate layer slurry;

[0058] 1.5 g of yttria-stabilized zirconia was used as a raw material, 0.2 ml of triethanolamine was used as a dispersant, 0.07 g of acrylic resin was used as a binder, 0.3 ml of polyethylene glycol-400 was used as a plasticizer, 2 ml of ethanol and 1 ml of butanone were used as solvents, and the mixture was stirred for 1 hour to obtain a yttria-stabilized zirconia electrolyte slurry;

[0059] 1.5g of perovskite material cobalt and strontium doped lanthanum ferrite La 0.6 Sr 0.4 Carbon monoxide 0.2Fe 0.8 O 3-δ As raw material, 0.2 ml triethanolamine as dispersant, 0.05 g polyvinyl butyral as binder, 0.2 ml dibutyl phthalate as plasticizer, 2 ml ethanol and 1 ml butanone as solvent were mixed and stirred for 1 hour to obtain a perovskite material cobalt and strontium doped lanthanum ferrite anode slurry;

[0060] d. Preparation of a nickel oxide-basalt cathode supported solid oxide electrolytic cell: spray the samarium-doped cerium oxide slurry prepared in step c onto the nickel oxide-basalt cathode support prepared in step b as an intermediate layer between the cathode and the electrolyte of the solid electrolytic cell, dry at room temperature for 12 hours, and calcine at a temperature of 1350°C in an air atmosphere for 6 hours; then spray the yttria-stabilized zirconium oxide slurry obtained in step c onto the intermediate layer of the solid electrolytic cell as an electrolyte, dry at room temperature for 12 hours, and calcine at a temperature of 1350°C in an air atmosphere. 6h; then spray the samarium-doped cerium oxide slurry obtained in step c on the electrolyte of the solid electrolytic cell as an intermediate layer between the electrolyte and the anode, dry at room temperature for 12h, and calcine at a temperature of 1350°C in an air atmosphere for 6h; finally, spray the perovskite material cobalt and strontium-doped lanthanum ferrite slurry obtained in step c on the samarium-doped cerium oxide intermediate layer of the solid electrolytic cell as an anode, dry at room temperature for 12h, and calcine at a temperature of 1350°C in an air atmosphere for 6h to obtain a nickel oxide-basalt cathode supported solid oxide electrolytic cell;

[0061] e. Preparation of a nickel-basalt cathode supported solid oxide electrolytic cell: The solid oxide electrolytic cell prepared in step d is sealed with alumina felt in a high-temperature furnace of a special electrolysis test equipment, and the temperature is raised to 750°C at a heating rate of 4°C / min, followed by introduction of 9% hydrogen / nitrogen for reduction for 3 hours to obtain a nickel-basalt cathode supported solid oxide electrolytic cell; 100 mL / min of carbon dioxide is introduced into the cathode side of the electrolytic cell, and the anode side is exposed to the air to provide voltage for the solid oxide electrolytic cell to electrolyze the carbon dioxide.

[0062] Conclusion: When the voltage is 1.6V, the current density is 216mA / cm 2 , the cathode conductivity is good, but the nickel particles are severely agglomerated and coarsened, resulting in pore blockage.

Claims

1. A method for preparing a nickel-basalt cathode supported solid oxide electrolytic cell, characterized in that: Follow these steps: a. Basalt pretreatment: crush the natural basalt ore for 40 min, pass it through a 100-mesh sieve to obtain basalt powder; then ball-mill the basalt powder for 12-20 h at a ball-milling speed of 150-300 rpm, pass it through a 400-mesh sieve to obtain uniform basalt powder particles; b. Preparation of nickel oxide-basalt cathode support: Grind the basalt powder particles obtained in step a and the nickel oxide powder in an agate mortar until they are uniformly mixed, the grinding time is 1 h, and then use a powder tablet press to press the mixed powder into a disc with a diameter of 40 mm and a thickness of 700-900 μm, the pressing pressure is 80-100 MPa, and the pressing time is 120 s; Calcine the disc at 1100-1350 ° C for 4-6 h to obtain a nickel oxide-basalt cathode support, wherein the mass proportion of nickel oxide powder is 50-80 wt%; c. Preparation of slurry: doping cerium oxide with samarium 0.2 Ce 0.8 O 2-δ As raw material, triethanolamine as dispersant, polyvinyl butyral as binder, dibutyl phthalate as plasticizer, ethanol and butanone as solvent, mixed and stirred for 1 h to obtain samarium-doped cerium oxide intermediate layer slurry; Yttria-stabilized zirconia was used as a raw material, triethanolamine was used as a dispersant, acrylic resin was used as a binder, polyethylene glycol-400 was used as a plasticizer, ethanol and butanone were used as solvents, and the mixture was stirred for 1 h to obtain a yttria-stabilized zirconia electrolyte slurry. Lanthanum ferrite La doped with cobalt and strontium perovskite materials 0.6 Sr 0.4 Carbon monoxide 0.2 Fe 0.8 O 3-δ As raw material, triethanolamine as dispersant, polyvinyl butyral as binder, dibutyl phthalate as plasticizer, ethanol and butanone as solvent, mixed and stirred for 1 h to obtain perovskite material cobalt and strontium doped lanthanum ferrite anode slurry; d. Preparation of a nickel oxide-basalt cathode supported solid oxide electrolytic cell: spray the samarium-doped cerium oxide slurry prepared in step c onto the nickel oxide-basalt cathode support prepared in step b as an intermediate layer between the cathode and the electrolyte of the solid electrolytic cell, dry at room temperature for 12 h, and calcine at a temperature of 1100-1350°C in an air atmosphere for 4-6 h; then spray the yttria-stabilized zirconia slurry obtained in step c on the intermediate layer of the solid electrolytic cell as an electrolyte, dry at room temperature for 12 h, and calcine at a temperature of 1100-1350°C in an air atmosphere for 4-6 h; then spray the samarium-doped cerium oxide slurry obtained in step c on the electrolyte of the solid electrolytic cell as an intermediate layer between the electrolyte and the anode, dry at room temperature for 12 h, and calcine at a temperature of 1100-1350°C in an air atmosphere for 4-6 h. h; finally, the cobalt- and strontium-doped lanthanum ferrite slurry of the perovskite material obtained in step c is sprayed on the samarium-doped cerium oxide intermediate layer of the solid electrolytic cell as an anode, dried at room temperature for 12 h, and calcined at a temperature of 1100-1350 ° C in an air atmosphere for 4-6 h to obtain a nickel oxide-basalt cathode supported solid oxide electrolytic cell; e. Preparation of a nickel-basalt cathode supported solid oxide electrolytic cell: the solid oxide electrolytic cell prepared in step d is sealed with alumina felt in a high-temperature furnace of a special electrolysis test equipment, and the temperature is raised to 750°C at a heating rate of 2-4°C / min, followed by introduction of 5%-10% hydrogen / nitrogen for reduction for 2-4 h to obtain a nickel-basalt cathode supported solid oxide electrolytic cell; 100 mL / min of carbon dioxide is introduced into the cathode side of the electrolytic cell, and the anode side is exposed to the air to provide voltage for the solid oxide electrolytic cell to electrolyze the carbon dioxide to obtain a nickel-basalt cathode supported solid oxide electrolytic cell.

2. Use of the nickel-basalt cathode supported solid oxide electrolytic cell obtained by the method according to claim 1 in the energy conversion process of preparing electrolytic carbon dioxide / water and solid oxide fuel cells.

Citation Information

Patent Citations

  • Nano composite cathode as well as preparation and application thereof

    CN111244470A

  • Fuel electrode for solid oxide electrolytic cell with improved high temperature electrolytic

    CN118007172A